Anisotropy of interstitial diffusion in bcc-crystals due to stress-induced unequal occupancies of different types of sites. (November 2018) - Svoboda, J.; Fischer, F.D.
Abstract: Deposition of an interstitial atom in octahedral or tetrahedral sites in a bcc-crystal provokes one of three types of local tensorial eigenstrains. Interaction of the interstitial atoms with an external and/or defect-generated stress state and their diffusion cause different occupancies of individual types of sites. The diffusion paths are analyzed for atoms occupying octahedral or tetrahedral sites. The current original model quantifies the anisotropy of diffusion by factors being functions of occupancies of individual types of sites. Coupling of this new model with a very recent model of interstitial diffusion, already accounting for various types of interstitial sites, provides a rather sophisticated theoretical model for simulation of interstitial diffusion in stressed crystals.